Antihyperlipidemic Effects of Sesamum indicum L. in Rabbits Fed a High-Fat Diet - Sedigheh Asgary; Mahmoud Rafieian-Kopaei; Somayeh Najafi; Esfandiar Heidarian; Amirhossein Sahebkar (The Scientific World Journal)
The present study aimed to investigate the anti-hyperlipidemic effects of sesame in a high-fat fed rabbit model. Animals were randomly divided into four groups of eight animals each for 60 days as follows: normal diet, hypercholesterolemic diet (1% cholesterol), hypercholesterolemic diet (1% cholesterol) + sesame seed (10%), and hypercholesterolemic diet (1% cholesterol) + sesame oil (5%). Serum concentrations of total cholesterol, LDL-C, HDL-C, triglycerides, apoA and apoB, SGOT, SGPT, glucose and insulin were measured at the end of supplementation period in all studied groups. Hypercholesterolemic feeding resulted in a significant elevation of TC, TG, LDL-C, HDL-C, SGOT and SGPT as compared to the normocholesterolemic diet group (P<0.05). Supplementation with sesame seed did not cause any significant alteration in lipid profile parameters, apolipoproteins, hepatic transaminases, glucose and insulin as compared to the hypercholesterolemic diet group (P>0.05). In contrast, rabbits supplemented with sesame oil were found to have lower circulating concentrations of TC, LDL-C, HDL-C, SGOT and SGPT (P<0.05), whilst concentrations of TG, apoA, apoB, insulin and glucose remained unaltered compared to the hypercholesterolemic diet group (P>0.05). Supplementation with sesame oil, but not sesame seed, can ameliorate serum levels of lipids and hepatic enzymes in rabbits under a high-fat diet.